Comparisons between neural response imaging thresholds, electrically evoked auditory reflex thresholds and most comfortable loudness levels in CII bionic ear users with HIRESOLUTION sound processing strategies. - Han D; Chen X; Zhao X; Kong Y; Li Y; Liu S; Liu B; Mo L (Acta Oto-Laryngologica, 2005)
CONCLUSIONS: The data collected in this study indicated that first Neural Response Imaging (NRI) thresholds had a better correlation with HiResolution most comfortable loudness (M) levels than tNRI thresholds. Electrically evoked auditory reflex thresholds (EARTs) had a higher correlation with HiResolution M levels than tNRI thresholds and a lower correlation than first NRI thresholds. NRI is a very useful method for programming the cochlear implants of young children who cannot demonstrate a reliable judgment of loudness. OBJECTIVE: To investigate how HiResolution sound processing, designed to deliver high-rate stimuli, relates to EARTs and electrically evoked compound action potential measurements produced by low-rate stimuli. MATERIAL AND METHODS: Nine profoundly hearing-impaired children and adults aged 6-29 years participated in the study. NRI responses were elicited using pulse trains consisting of biphasic pulses at a pulse width per phase of 32 micros delivered at a frequency of 30 Hz using SoundWave programming software. Stimuli were delivered to the odd electrodes (1, 3, 5, 7, 9, 11, 13 and 15) along the array. tNRI (NRI threshold) and first NRI thresholds were recorded for each stimulating electrode. 'Speech bursts' stimuli used in EARTs recording were delivered to four electrodes at a time and stapedial reflexes were recorded from the impedance bridge. The M levels used were those used by each patient in their everyday HiResolution programs. RESULTS: For 8 patients (53 stimulating electrodes) the correlation between tNRI threshold and M level was r=0.675 (p=0.000) and that between first NRI thresholds and M level was r=0.741 (p=0.000). On average the M-level value was 20 CU (Current Unit) lower than the first NRI threshold value and 12 CU higher than the tNRI threshold value. The M-level patterns across the electrode array overall were similar to the tNRI or first NRI threshold patterns. For 7 patients (112 stimulating electrodes) the correlation between EART and M levels was r=0.710 (p=0.000). On average the EART value was 14 CU higher than the M-level value.